Autonomic Dysreflexia After Hip Fractures Managed by Regional Anesthesia: A Case Report. Issue 1 (January 2022) - Huynh, Alexander; Ryan, Rabiul; Patel, Rohan; Molina, Alan; Olson, Alexander M.; Schwenk, Eric S.
Abstract : Autonomic dysreflexia occurs after a spinal cord injury usually at the level of T6 or above, and its hallmark feature is exaggerated autonomic response to noxious stimuli resulting in uncontrolled hypertensive episodes with reflexive bradycardia that can be fatal if not controlled. We present a case highlighting regional anesthetic techniques, including peripheral nerve blocks, to ameliorate the symptoms of autonomic dysreflexia triggered by hip fractures in a 57-year-old woman with an old C5-C6 spinal cord injury before definitive hip surgery. The regional techniques described provide anesthesiologists with a simple strategy to potentially mitigate a life-threatening situation.